Live Images of Donor Dendritic Cells Trafficking via CX3CR1 Pathway - Ueno, Takuya; Kim, Pilhan; McGrath, Martina M.; Yeung, Melissa Y.; Shimizu, Tetsunosuke; Jung, Keehoon; Sayegh, Mohamed H.; Chandraker, Anil K.; Abdi, Reza; Yun, Seok H. (Frontiers in Immunology, 2016)
Background: A number of studies have demonstrated the role of CX3CR1 in regulating the migration of monocytes into peripheral tissue and their transformation into DC. No data are yet available on the importance of chemokine pathways in regulating homeostasis of dendritic cell (DC) in heart transplants. Recently, we showed that recipients of heart allografts from CXC3R1-/- donors show longer survival. To dissect the role of CX3CR1 signaling in the homeostasis of heart dDC, we have developed and tested a novel in vivo imaging tool in CX3CR1GFP/+ DC (B6 background) heart graft into BALB/c recipient model. Results: Majority of GFP positive cells located in the middle of cardiac myocyte and their shapes were stretching and still roundish in the early phase of post transplant (3 and 24hours). However, images from 72hours at cardiac graft showed many of GFP positive cells move to vessel areas. In addition, significant immunological events such as GFP positive cell exiting from cardiac myocyte and changes of GFP positive cell motility and shape were detected. GFP positive cells were detected in the vasculature and lymph nodes. Only 1 GFP positive cell was observed in three lymph nodes (2 mesenteric, 1 inguinal) (72hours). Conclusions: Current data will define the function of dDC in regulating alloimmune responses in vivo and provide information to develop novel strategies designed to achieve durable tolerance and prevent chronic rejection.